A Study on Balaikhuti Beel Fish Diversity in Kalgachia, Barpeta, Assam - Khatun, Afliuja; Gogoi, Jayanta; Hussain, Bakhtiar; Choudhury, Prasanta Kumar; Sengupta, Saibal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Balaikhuti beel, a substantial wetland of Barpeta district of Assam underwent a thorough examination of fish diversity in the current study. The present study was conducted to assess the fish diversity in Balaikhuti Beel’ located in the Barpeta district of Assam, as well as to evaluate the current status of the fish population in the beel. Systematic collection of fish samples was made at six distinct sampling stations, with their diversity status evaluated. The investigation revealed a diverse ecosystem, housing 42 fish species spanning across 16 families. Significantly, the Cyprinidae emerged as the predominant group, exhibiting the highest occurrence percentage. Among the recorded species, Puntius sophore (Pool Barb) and Labeo calbasu (Orange-fin Labeo) stood out as the largest contributors, while minor-sized fish formed the bulk of the catch. Within the assessed categories of IUCN five fish were identified as Threatened, one Near Threatened, 34 Least Concern and two not evaluated (NE). Notably, the beel also harboured five exotic fish species, with Clarias gariepinus (African Sharp-tooth Catfish) making the debut record in Assam’ beel.